2000
DOI: 10.1103/physrevlett.85.5130
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Anomaly in High-Pressure Zn

Abstract: The equation of states and phonon dispersions of hexagonal zinc have been calculated by the plane-wave pseudopotential method within the generalized-gradient approximation. Weak discontinuities are found in the pressure-volume relation as well as the c/a-volume curve. Phonon dispersions of Zn under pressure have been obtained with a direct method and the results are consistent with the neutron scattering data. At V/V0 approximately 0.88, the calculated frequencies of the acoustic phonons near the zone center s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
(43 reference statements)
2
33
0
Order By: Relevance
“…A computational study on bcc Nb under pressure showed that topological transitions occur at 5 and 60 GPa [367], consistent with measurements of pressure-induced changes in the superconducting transition temperature [368]. A computational study on hcp Zn showed an electronic topological transition at high compression that was responsible for a change in compressibility and the axial ratio of the structure [369]. Experimental evidence for a change in phonon frequencies in Zn was found by inelastic neutron scattering at a pressure of approximately 6.8 GPa [362], but the effect on elastic constants has been questioned [370].…”
Section: Kohn Anomalies and Electronic Topological Transitionsmentioning
confidence: 57%
“…A computational study on bcc Nb under pressure showed that topological transitions occur at 5 and 60 GPa [367], consistent with measurements of pressure-induced changes in the superconducting transition temperature [368]. A computational study on hcp Zn showed an electronic topological transition at high compression that was responsible for a change in compressibility and the axial ratio of the structure [369]. Experimental evidence for a change in phonon frequencies in Zn was found by inelastic neutron scattering at a pressure of approximately 6.8 GPa [362], but the effect on elastic constants has been questioned [370].…”
Section: Kohn Anomalies and Electronic Topological Transitionsmentioning
confidence: 57%
“…Li and Tse confirmed the c/a anomaly, although the magnitude of their anomaly is much smaller than other calculations. 12 Steinle-Neumann et al pointed out that the c/a anomaly is very sensitive to the Brillouin-zone sampling, and should disappear if a sufficient number of k points is used for the calculation. 13 Kechin studied details of the ETTs at the K and L symmetry points of the Brillouin zone.…”
mentioning
confidence: 99%
“…With increasing pressure, the low-frequency optical phonon branch gradually softens at the at H point. This phonon softening may be because of the ETT transition described above [29]. In contrast, the acoustic phonon branches harden with increasing pressure.…”
Section: The Lattice Dynamical Properties Of Malsimentioning
confidence: 92%